The Vietnam provincial governance and public administration performance index (PAPI) 2011 : (United Nations Development Programme (UNDP), 2011)
“People know, people discuss, people do and people verify” is a Vietnamese phrase that perhaps best summarizes the goals of the Provincial Governance and Public Administration Performance Index (PAPI). PAPI provides objective information about citizens’ experiences and interactions with local authorities, thus “people know”. It provides a means for the discussion and validation of findings at central and local levels in order for people to discuss. PAPI illuminates the collective experience of what citizens do, enabling policy makers to act in their interests, thereby fulfilling the precept that “people do”. Finally, PAPI provides a tool to assess actual administrative performance allowing people to verify.